Exploring Students’ Learning Strategies in EFL Learning - Muhammad Fikri Taufik; Eva Meidi Kulsum; Wawa Puja Prabawa (UIN Sunan Gunung Djati Bandung, 2023)
The purpose of this study was to describe students’ learning straties in an English as a Foreign Langauge (EFL) learning used by social and science students in certain senior high school in Sumedang. Students of grade 11 were chosen as participant of this research. 9 students of social and 9 students of science were selected as the sample of this research. This research is categorized as qualitative research using questionnaire from Oxford (1990) as the instruments and followed up by semi-structured interview to confirm the result from questionnaire. It is found that there are 6 strategies used by both social and science students. They are memory, cognitive, compensation, metacognitive, affective, and social strategies. Based on the data found, the researcher concluded that most of social students frequently use social, cognitive, and affective strategies, while most of science students frequently use metacognitive, cognitive, and compensation strategies. In essence, each student has a different way of learning. they have their advantages and disadvantages. Since it is known that learning strategies are importnat it is suggested for teacher to train students to use language learning strategies that can help them become better language learners.